USE OF DIGITAL ENCYCLOPEDIA MEDIA TO DEVELOP COGNITIVE ASPECTS OF EARLY CHILDHOOD - dian supriatin (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2018)
Abstract Early childhood education is essentially education organized with the aim to facilitate the growth and development of children as a whole. Cognitive development refers to the child's development in thinking and the ability to give reasons. Digital encyclopedia media is one of the supporting activities in playing, because through these media children can find out a lot of things by looking at pictures, writing, listening to sounds, also can grow cognitive development or knowledge of children about everything that is found or not around their environment .The research method used in this study is descriptive with qualitative analysis with data collection techniques through observation of four students with age groups 5 to 6 years and interviews with two teachers, documentation and literature. The objectives of this study are: (1) to describe the planning of using digital encyclopedia media to develop cognitive aspects of early childhood, (2) to know the use of digital encyclopedia media in developing cognitive aspects of early childhood, (3) knowing the results of the application of media encyclopedia digital in developing cognitive aspects of early childhood (4) knowing the factors that become difficulties or obstacles in the use of digital encyclopedia media. Keywords: Early Childhood, Cognitive Development, Digital Media Encyclopedia